Despite Antagonism in vitro, Pseudomonas aeruginosa Enhances Staphylococcus aureus Colonization in a Murine Lung Infection Model - Millette, Guillaume; Langlois, Jean-Philippe; Brouillette, Eric; Frost, Eric H.; Cantin, André M.; Malouin, François (Frontiers in Microbiology, 2019)
Staphylococcus aureus and Pseudomonas aeruginosa are prevalent lung pathogens in cystic fibrosis (CF). Whereas co-infection worsens the clinical outcome, prototypical strains are usually antagonistic in vitro. We sought to resolve the discrepancy between these in vitro and in vivo observations. In vitro, growth kinetics for co-cultures of co-isolates from CF patients showed that not all P. aeruginosa strains affected S. aureus viability. On solid media, S. aureus slow-growing colonies were visualized around some P. aeruginosa strains whether or not S. aureus viability was reduced in liquid co-cultures. The S. aureus-P. aeruginosa interactions were then characterized in a mouse lung infection model. Lung homogenates were plated on selective media allowing colony counts of either bacterium. Overall, 35 P. aeruginosa and 10 S. aureus strains (clinical, reference and mutant strains), for a total of 200 co-infections, were evaluated. We observed that S. aureus colonization of lung tissues was promoted by P. aeruginosa and even by strains showing antagonism in vitro. Promotion was proportional to the extent of P. aeruginosa colonization, but no correlation was found with the degree of myeloperoxidase quantification (as marker of inflammation) or with specific virulence-associated factors using known mutant strains of S. aureus and P. aeruginosa. On the other hand, P. aeruginosa significantly increased the expression of two possible cell receptors for S. aureus, i.e., ICAM-1 and ITGA-5 (marker for integrin α5β1) in lung tissue, while mono-infections by S. aureus did not. This study provides insights on polymicrobial interactions that may influence the progression of CF-associated pulmonary infections.